Política pública e educação digital no ensino fundamental em Natal/RN: análise de eficácia da atuação dos objetivos do Proinfo Municipal - Martins, Iris Laura Batista (2010)
The present work turns on the public politics of digital inclusion and of the impact of the Technologies of the Information and Communication in the formation of the citizenship. For this, it was opted for doing an analysis of effectiveness of the performance of the objectives of the Proinfo (National Program of Computer Science in the Education) municipal district of Natal-RN. As instrument of collection of data, three types of questionnaires were used. The collected data were analyzed and discussed starting from it analyzes it descriptive of averages and analyze of multiple regression. The results of the research pointed that the teachers and the students use the computer science in a restricted way. On the other hand, the digital education is not still totally contemplated in the schools beneficiaries' digital rérumé by Proinfo municipal and thus, the inefficacy of the program was verified with relationship the educational training and the students' digital inclusion